STABILITAS PEMERIKSAAN HEMATOLOGI RUTIN PADA SAMPEL DARAH YANG DIDIAMKAN PADA SUHU RUANG MENGGUNAKAN CELL-DYN RUBY - Gilang Nugraha; Nur Anita Ningsih; Titik Sulifah; Sitti Fitria (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST, 2021)
Complete blood count (CBC) is one of the laboratory tests most often influenced by doctors. The use of a hematology analyzer offers a wider range of probe parameters. The pre-analytic stage accounts for 70% of errors, one of which is the delay of the examination. Changes in report results were reported due to changes in blood cell morphology due to EDTA additives and room temperature. The aim of this research is the disturbance of stability of the results of examination of various CBC parameters in blood samples that are left at room temperature for 24 hours using a hematology analyzer. This experimental laboratory research was conducted at the Pramita Jemur Andayani Clinical Laboratory. Blood samples were obtained from volunteers, stored at room temperature and subjected to immediate examination (control) and after a delay of 6, 12 and 24 hours (treatment). A total of 30 respondents, consisting of 8 men and 22 women. The mean age of the respondents was 22 ± 1 year. There was no difference in the results of the examination (p-value > 0.05) in the RBC, Hct MCV, MCHC, PLT and PDW. The results of the examination (p-value < 0.05) were found on Hgb, MCH, RDW, WBC, NEU, IG, MONO, EO, BASO, LYM, PLT and PDW. Delayed CBC examinations using the CELL-DYN Ruby hematology analyzer directly gave different results on several parameters ranging from 6 hours delay of examination.